Pengaruh kompetensi pengguna sistem informasi akuntasi terhadap kualitas informasi akuntansi - Maulana, Fajar (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
In this era of globalization, information can be interpreted as data that is processed and managed with the intention of giving meaning and helping the decision-making process. This study intends to examine the effect of the variable ability of AIS users (Accounting Information Systems) on the variable quality of accounting information. This research is quantitative and uses descriptive and verification methods using survey techniques. The researcher used nonprobability sampling with saturated sampling, with 30 accounting and system employees from PT. ABC and XYZ, both food and beverage industry companies in Bandung Regency, as samples and respondents. The data analysis technique uses simple linear regression with a questionnaire data collection technique. The results of this study concluded that there is a significant influence between the competency variables of accounting information system users (AIS) and the quality of accounting information.